Candida albicans and Candida dubliniensis Show Different Trailing Effect Patterns When Exposed to Echinocandins and Azoles - Ayadi, Rania; Sitterlé, Emilie; d’Enfert, Christophe; Dannaoui, Eric; Bougnoux, Marie-Elisabeth (Frontiers in Microbiology, 2020)
When Candida albicans and Candida dubliniensis isolates were tested for susceptibility to fluconazole and echinocandins using either EUCAST or Etest methods, differential patterns of growth were observed, independently of the methods used. For C. albicans, a trailing phenomenon (incomplete growth inhibition at supra-MICs) was observed with fluconazole in 90% and 93.3% for EUCAST and Etest, respectively, but not with echinocandins (<7% for EUCAST and 0% for Etest). In contrast, for C. dubliniensis, a trailing phenomenon was very rarely observed with fluconazole (20% for EUCAST and 0% for Etest), while the opposite pattern was observed with echinocandins (>50% for EUCAST and >86% for Etest). This suggests that the pathways involved in the trailing effect might be different between these two related species. Furthermore, clinical microbiologists must be aware of these species-specific patterns for a reliable MIC determination.